Analisis Produk Pembiayaan Mitraguna di Bank Syariah Indonesia (BSI) Kantor Cabang Pembantu (KCP) Banjarnegara Berdasarkan Fatwa DSN MUI No:04/DSN/MUI/IV/2000 Tentang Murabahah - Azizah, Khusnul; Naufal, Naufal Kurniawan (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2023)
Banking is an institution that has an important role in helping meet people's living needs. Sharia banking is a very effective alternative for carrying out banking transactions without interest. Because, sharia banking is part of sharia financial institutions which have various financing products and services and are run based on sharia principles. One of the financing products provided by sharia banks is partner financing with a murabahah contract which aims to meet the consumptive needs of the community in a halal manner and based on sharia principles. Therefore, the main problem taken in this research is the mechanism of partner financing at Bank Syariah Indonesia (BSI) Banjarnegara Sub-Branch Office (KCP) as well as the analysis of partner financing products therein based on DSN MUI Fatwa No: 04/DSN/MUI/IV/ 2000 Concerning Murabahah. This research is field research, namely research that explores data from the field by interviewing sources using qualitative descriptive methods. Primary data was obtained by interviews while secondary data was taken from books or articles related to research. The data collection process was carried out using observation, interviews and documentation methods. Test the validity of the data using source traingulation and techniques. The results of this research show that partner financing products are implemented in four stages, namely: submitting a financing application, assessing the feasibility of financing, checking files/verifying data, and disbursing financing. And partner financing products at Bank Syariah Indonesia (BSI) Sub-Branch Offices (KCP) are generally in accordance with DSN MUI Fatwa No:04/DSN/MUI/IV/2000 concerning Murabahah. However, there are points that are not appropriate, namely in the implementation of the wakalah contract which should be carried out before the murabahah contract.